Behavioral Patterns of Placement of CIN (Children In Need) and Regular Students in Inclusive Classes Learning - Rizki Nur Kalifah, Diah; Sri Nugraheni, Aninditya (Al-Athfal: Jurnal Pendidikan Anak, 2022)
Purpose – In one school institution, there is two formal education consisting of CIN and regular students so that social inequality does not occur, and the same pattern of behavior is applied without distinguishing students’ shortcomings. This study aimed to analyze the behavior patterns of placement of students with special needs and regular students in learning in inclusive classes.Design/methods/approach – The method used in this research is the qualitative method of the Miles and Huberman case study. The population and sample in this study were 8 grade IV elementary school teachers, while the sampling technique was carried out using the proportional sampling method. The types of research data are primary and secondary, while the research data collection techniques are carried out by observation, interviews, and recording methods. The research stages include data reduction; data analysis starts from teacher planning in learning, evaluation of learning in inclusive classes, as well as teacher behavior patterns during the learning process for students with special needs and regular students; data verification or conclusions are drawn by reporting the results of the analysis.Findings – The research findings prove that the behavior to not differentiate between CIN and regular students is to use group learning methods consisting of CIN and regular students and to instill character education in CIN students, and through a motivational approach that strengthens the confidence of CIN students to partner with regular students.Research implications/limitations – This study was limited to where inclusive schools must prepare everything, be it teachers, students, or learning tools. Practical implications – Pattern behavior placement CIN and regular students in learning same without distinguishing and see the social status, physical, and intellectual intelligence. The differences are not in behavior patterns but learning tools such as syllabi, lesson plans, and exam questions. Teachers and students have stable values and a sense of tolerance for the differences and drawbacks of CIN students.Originality/value – In one class with special and regular students, learning activities are only in inclusive schools but in formal, informal, and non-formal schools. Paper type Case study